Inclusion body myositis: clinical review and current practice. (December 2014) - Brady, Stefen; Healy, Estelle G; Machado, Pedro; Parton, Matt; Holton, Janice L; Hanna, Mike G
Inclusion body myositis (IBM) is the commonest acquired myopathy in individuals aged over 50 years. The first description of a patient with IBM was published in 1967. Despite much research into the illness, our understanding is far from complete and IBM remains an enigmatic and often misdiagnosed condition for which there is currently no effective drug treatment. However, new pathological findings, the recent identification of muscle-specific serum auto-antibodies and the increasing use of MRI in patients with IBM are important advances that may lead to earlier diagnosis and improved understanding of the disease. The purpose of this review is to provide an update on the scientific developments in IBM with particular emphasis on current and future clinical trials.